Difficulties of financing public universities and means of dealing with them under the general budget of the state: بحث تطبيقي في الجامعة المستنصرية - Ali, Khalid S.; Jaeilo, Karima Abbas (Journal of University of Human Development, 2018)
One of the most important challenges facing higher education institutions in the international arena is the challenge of financing. The problems of financing are complicated by the growing trend of increasing efficiency and quality effectiveness. The research aims to uncover the problems of funding in public universities and provide future proposals that help to solve its difficulties. The research problem stems from the problem of deficit in the budgets of public university education and its high cost and funding difficulties facing increasing expenditure because of its dependence on the general budget of the state. The research was based on the basic hypothesis that "the adoption of public universities on a variety of funding sources will help to solve the difficulty of funding through the model and proposals adopted to develop sources of funding and rationalization of spending”. The research concluded a number of conclusions, the most prominent of which were Increasing the need of public universities for financial resources to meet their various needs, Poor efficiency of funding management in public universities, and the adoption of financing of university education almost entirely dependent on the state budget. Based on the results, the recommendations of the research are the need to review the method used in the preparation of budgets as it is the basis in the process of controlling revenues and directing expenditures, as well as the need to link government support to universities achievements, and make universities production centers and through the application of the concept of productive university and work on increasing Efficiency of spending through the optimal use of human competencies and technology.